HUMAN CAPITAL INDICATORS IN SERVICE INDUSTRIES: FROM WORKFORCE PROFILE TO OUTPUT MEASURES - Skapska, Elzbieta; Samul, Joanna (European Scientific Journal, ESJ, 2015)
Human capital is an especially important attribute of business activity of all types of enterprises and continuously constitutes a trending subject among theoreticians. Continually arising new theories and methods of human capital measurement do not meet with sufficient interest and confirmation of their significance among practitioners. Market reality makes service organizations notice the need for being interested in the research regarding human capital. This article is an attempt to determine instruments for measuring human capital which is used for providing services by an organization. The research focused on the service sector because of its intellectual and personnel intensive nature. The final sample consisted of 93 Polish firms. This study presents the perception of the importance to disclose human capital measures by senior executives in service firms and shows what they concentrate on – measure of age, competency level, engagement, productivity, customer service or satisfaction